Fixed-combination halobetasol propionate and tazarotene topical lotion decreases TNF-α and IL-17A levels in psoriatic lesions - Zoe Diana Draelos; Matthew M. Draelos; Tina Lin; Abby Jacobson (Taylor & Francis Group, 2023)
Objective Fixed-combination halobetasol propionate (0.01%) and tazarotene (0.045%) lotion (HP/TAZ) is approved for the treatment of plaque psoriasis in adults, with a demonstrated efficacy and safety profile in phase 3 trials. This study examined the effect of HP/TAZ on the reduction of tumor necrosis factor alpha (TNF-α) and interleukin 17 A (IL-17A) and its correlation to psoriasis improvement. Materials and methods Ten adults with mild-to-moderate plaque psoriasis and 2 symmetrical plaques self-applied HP/TAZ (treated plaque) or vehicle lotion (untreated plaque) for 12 weeks. At baseline and each study visit (weeks 2, 4, 8, and 12), Investigator's Global Assessment (IGA) score and erythema, scaling, and induration were assessed. Additionally, D-squame tape strips were utilized to quantify TNF-α and IL-17A in target lesions by enzyme-linked immunosorbent assay. Results Significant improvements in mean IGA score in HP/TAZ-treated compared with untreated plaques were evident at week 2 and maintained through week 12 (p < 0.003). HP/TAZ significantly reduced TNF-α levels at weeks 4 through 12 (p < 0.03) and IL-17A levels at weeks 2 through 8 (p < 0.05) in treated compared with untreated plaques. Conclusions HP/TAZ was highly effective in treating psoriasis plaques and, although HP/TAZ is not a biologic, effectively reduced cytokine-associated inflammatory markers that drive psoriatic disease.